Delivering aid without government : international aid and civil society engagement in the recovery and reconstruction of the Gaza Strip - Qarmout, Tamer (Springer, 2017)
In a fragile and conflict-ridden context such as the Gaza Strip, where the de facto Hamas government faces isolation and lacks international recognition, the provision of aid and development schemes challenges donors and CSOs delivering services to Palestinians. This volume examines how international donors influenced the reconstruction and recovery policy agenda as well as its implementation. Moreover, as a result of the no-contact policy, recovery and reconstruction schemes were delivered with limited involvement from the de facto Hamas government, raising questions about the efficacy of the "governance without government" concept. This book examines the dynamics and the impact of international donors' financing of Civil Society Organizations that were involved in the reconstruction of the Gaza Strip. It expands on the existing analysis of transnational aid actors' influence found in the public policy literature while contributing to our understanding of the concrete, and more specific, impact of international donors' financing on the livelihoods of the Palestinian people.
Keywords: International relief -- Gaza Strip.; Non-governmental organizations -- Gaza Strip.; Gaza Strip -- Politics and government.; Gaza Strip.; elektronické knihy; electronic books